Evaluation of Indian Information Technology Companies’ Economic Performance (International Journal of Scientific Research in Science and Technology, 2024)
The present study evaluates the efficiency of five organizations within India’s Information Technology (IT) sector, selected based on their market capitalization. The analysis focuses on key factors such as Sales, Profit After Tax, Long Term Debt to Equity, Interest Coverage, Working Capital, Debtors, Employee Turnover, and Cash Reserves, over a period of 10 years. The results indicate that all organizations have shown robust performance in Sales and Profit After Tax. These companies are primarily equity-financed and have no issues meeting their interest obligations. The outcomes related to working capital are satisfactory, and all firms maintain substantial cash reserves. Except for Tech Mahindra, which exhibits fluctuations, the companies demonstrate consistent performance across various metrics.